HUBUNGAN ANTARA KESEIMBANGAN KEHIDUPAN-KERJA DAN INTENSI TURNOVER KARYAWAN - Anisa Hasna Tsabitah; Puti Archianti Widiasih (program studi psikologi, 2025)
Quiet quitting is a phenomenon where employees only do their jobs according to jobdesc without any extra effort to serve the job. Quiet quitting is considered very closely related to work-life balance, when employees have work-life balance at they work and life, then they will survive and focus on every their task and responsibility. The inability of an employee to achieve his work-life balance affects the desire to quit his job (turnover intention). Previous studies on work-life balance and turnover intentions have shown conflicting results, so this study aims to determine whether or not there is a relationship between work-life balance and turnover intentions. This study used a quantitative approach with non-probability sampling and incidental sampling techniques through questionnaires. The respondents amounted to 165 employees at PT XYZ. Data collection using The relation between work-family balance and quality of life (WLB) scale, and turnover intention scale. The data were analyzed using the classical assumption test and the Pearson correlation hypothesis test. The results of the test showed that there was a significant relationship between work-life balance and turnover intentions and the direction of relationship is negative.